Government Expenditure and Economic Growth in South Africa: A Vector Error Correction Modelling and Granger Causality Test - Molefe, Kagiso; Choga, Ireen (Journal of Economics and Behavioral Studies, 2017)
Previous studies generally find mixed empirical evidence on the relationship between government spending and economic growth. This study re-examine the relationship between government expenditure and economic growth in South Africa for the period of 1990 to 2015 using the Vector Error Correction Model and Granger Causality techniques. The time series data included in the model were gross domestic Product (GDP), government expenditure, national savings, government debt and consumer price index or inflation. Results obtained from the analysis showed a negative long-run relationship between government expenditure and economic growth in South Africa. Furthermore, the estimate of the speed of adjustment coefficient found in this study has revealed that 49 per cent of the variation in GDP from its equilibrium level is corrected within of a year. Furthermore, the study discovered that the causality relationship run from economic growth to government expenditure. This implied that the Wagner’s law is applicable to South Africa since government expenditure is an effect rather than a cause of economic growth. The results presented in this study are similar to those in the literature and are also sustained by preceding studies.